Exchange Rates and Economic Fundamentals : A Framework for Analysis - Symansky, Steven (Occasional Papers; Occasional Paper, 1994)
This paper summarizes the methods and types of indicators that are often employed, both insid and outside the IMF, to assess whether exchange rates are broadly in line with economic fundamentals.